Scandium-doped zinc cadmium oxide as a new stable n-type oxide thermoelectric material. Issue 31 (21st July 2016) - Han, L.; Christensen, D. V.; Bhowmik, A.; Simonsen, S. B.; Hung, L. T.; Abdellahi, E.; Chen, Y. Z.; Nong, N. V.; Linderoth, S.; Pryds, N.
Abstract : Scandium-doped zinc cadmium oxide is proposed as a new n-type oxide thermoelectric material, which is stable in air at high temperature up to 1073 K, and having a 7-fold-reduced thermal conductivity at RT and the highest ZT ∼0.3 at 1173 K. Abstract : Scandium-doped zinc cadmium oxide (Sc-doped ZnCdO) is proposed as a new n-type oxide thermoelectric material. The material is sintered in air to maintain the oxygen stoichiometry and avoid instability issues. The successful alloying of CdO with ZnO at a molar ratio of 1 : 9 significantly reduced the thermal conductivity by up to 7-fold at room temperature. By carefully selecting the Sc-dopant concentrations, a high power factor of 7.1 × 10 −4 W m −1 K −2 at 1173 K could be obtained. Therefore, the highest ZT ∼ 0.3 at 1173 K was achieved for the Zn0.9 Cd0.1 Sc0.01 O1.015 sample, and it has so far one of the highest ZT values among those reported for ZnO based thermoelectric materials over the temperature range, e.g., its ZT value at 300 K, which is 0.012, is over 1 order of magnitude higher than that of the state-of-the-art nanostructured Al-doped ZnO, which is 0.0013. It suggests that this material is a good candidate for improving the overall conversion efficiencies in oxide thermoelectric modules. Meanwhile, Sc-doped ZnCdO is robust in air at high temperatures, whereas other n-type materials, such as Al-doped ZnO, will experience rapid degradation of their electrical conductivity and ZT .